Hemoglobin A clearance in children with sickle cell anemia on chronic transfusion therapy. Issue 6 (17th April 2018) - Yee, Marianne E. M.; Josephson, Cassandra D.; Winkler, Anne M.; Webb, Jennifer; Luban, Naomi L.C.; Leong, Traci; Stowell, Sean R.; Roback, John D.; Fasano, Ross M.
Abstract : BACKGROUND: Chronic transfusion therapy for sickle cell anemia reduces disease complications by diluting sickle‐erythrocytes with hemoglobin A (HbA)‐containing erythrocytes and suppressing erythropoiesis. Minor antigen mismatches may result in alloimmunization, but it is unknown if antigen mismatches or recipient characteristics influence HbA clearance posttransfusion. STUDY DESIGN AND METHODS: Children with sickle cell anemia on chronic transfusion therapy were followed prospectively for 12 months. All patients received units serologically matched for C/c, E/e, and K; patients with prior red blood cell (RBC) antibodies had additional matching for Fy a, Jk b, and any previous alloantibodies. Patients' RBC antigen genotypes, determined by multiplexed molecular assays (PreciseType Human Erythrocyte Antigen, and RHCE and RHD BeadChip, Immucor) were compared to genotypes of transfused RBC units to assess for antigen mismatches. Decline in hbA (ΔHbA) from posttransfusion to the next transfusion was calculated for each transfusion episode. RESULTS: Sixty patients received 789 transfusions, 740 with ΔHbA estimations, and 630 with donor Human Erythrocyte Antigen genotyping. In univariate mixed‐model analysis, ΔHbA was higher in patients with past RBC antibodies or splenomegaly and lower in patients with splenectomy. RBC antigen mismatches were not associated with ΔHbA. In multivariate linear mixed‐effects modeling, ΔHbA was associated with RBC antibodies (2.70 vs. 2.45 g/dL/28 d, p = 0.0028), splenomegaly (2.87 vs. 2.28 g/dL/28 d, p = 0.019), and negatively associated with splenectomy (2.46 vs. 2.70 g/dL/28 d, p = 0.011). CONCLUSIONS: HbA decline was increased among patients with sickle cell anemia with prior immunologic response to RBC antigens and decreased among those with prior splenectomy, demonstrating that recipient immunologic characteristics influenced the clearance of transfused RBCs.